The Effectiveness of Mindfulness-Based Schema Therapy on Anxiety , Quality of life and Frustration Tolerance of Patients with Multiple Sclerosis - Niloofar Jafarian; Ali Rezaie; Fatemeh Izadi (روانشناسی بالینی و شخصیت)
Introduction: Multiple sclerosis is a progressive neurological disease that leads to various disabilities in affected individuals. The combination of symptoms and the chronic nature of this condition can significantly impact a person's mental well-being, contributing to broader psychological issues related to the progression of the disease. Consequently, the aim of the present study was to investigate the effectiveness of mindfulness-based schema therapy on anxiety, quality of life, and frustration tolerance in patients with multiple sclerosis. Method: This study employed a quasi-experimental pre-test-post-test design with a control group. The statistical population consisted of individuals with multiple sclerosis in Shahrekord. A total of 30 participants were purposefully selected and randomly assigned to either the experimental or control group. The intervention was conducted in a group format over eight sessions for the experimental group. The instruments utilized in the study included Young's Primary Maladaptive Schemas Questionnaire, the Beck Anxiety Inventory (BAI), the MS Quality of Life Scale (MSQOL), and the Harrington Frustration Tolerance Questionnaire. Participants completed these assessments during both the pre-test and post-test phases. Data analysis was performed using analysis of covariance (ANCOVA).Results: The results indicated that 97.3% of the changes were associated with anxiety reduction, 96.8% with improvements in frustration tolerance, and 98.5% with enhancements in quality of life during the post-test phase. These changes were attributed to the effects of mindfulness-based schema therapy, which resulted in decreased anxiety, increased quality of life, and improved frustration tolerance (p < 0.001). Discussion and conclusion: The results indicate that mindfulness-based schema therapy significantly reduced anxiety, enhanced quality of life, and increased frustration tolerance in the experimental group when compared to the control group.